Indirect calorimetry in nutritional therapy. A position paper by the ICALIC study group. Issue 3 (June 2017) - Oshima, Taku; Berger, Mette M.; De Waele, Elisabeth; Guttormsen, Anne Berit; Heidegger, Claudia-Paula; Hiesmayr, Michael; Singer, Pierre; Wernerman, Jan; Pichard, Claude
Summary: Background & aims: This review aims to clarify the use of indirect calorimetry (IC) in nutritional therapy for critically ill and other patient populations. It features a comprehensive overview of the technical concepts, the practical application and current developments of IC. Methods: Pubmed-referenced publications were analyzed to generate an overview about the basic knowledge of IC, to describe advantages and disadvantages of the current technology, to clarify technical issues and provide pragmatic solutions for clinical practice and metabolic research. The International Multicentric Study Group for Indirect Calorimetry (ICALIC) has generated this position paper. Results: IC can be performed in in- and out-patients, including those in the intensive care unit, to measure energy expenditure (EE). Optimal nutritional therapy, defined as energy prescription based on measured EE by IC has been associated with better clinical outcome. Equations based on simple anthropometric measurements to predict EE are inaccurate when applied to individual patients. An ongoing international academic initiative to develop a new indirect calorimeter aims at providing innovative and affordable technical solutions for many of the current limitations of IC. Conclusion: Indirect calorimetry is a tool of paramount importance, necessary to optimize the nutrition therapy of patients with various pathologies and conditions. Recent technical developments allow broader use of IC for in- and out-patients.